Long-term high-resolution multi-drought indices datasets for Austria derived from ERA5 Land ReanalysisMendeley Data - Jakob Ernst; Milica Stojanovic; Rogert Sorí (Data in Brief)
Dry and wet spells are among the most dangerous environmental phenomena worldwide, with a documented rise in both frequency and severity in recent decades. Austria is no exception to this trend. This study presents a long-term, high-resolution multi-drought indices dataset for Austria to enhance drought and wet period monitoring and impact assessment. The dataset includes six established drought indices: the Standardised Precipitation Index (SPI), the Standardised Precipitation-Evapotranspiration Index (SPEI), the self-calibrating Palmer Drought Severity Index (scPDSI), the Reconnaissance Drought Index (RDI), the modified Reconnaissance Drought Index (RDIe), and the Vapour Pressure Deficit (VPD). These indices are calculated monthly for the period 1950 – 2023, using Reanalysis ERA5-Land data with a horizontal resolution of 0.1°. The multiscale indices are calculated over different timescales (1 to 48 months), providing a comprehensive view of hydroclimatic variability and representing various drought types (meteorological, agricultural, and hydrological). The data are available in diverse formats, allowing for flexible spatial and temporal analyses. The 2003 drought event, one of the most severe in Austria's recent history, serves as an example to illustrate the performance and consistency of the indices. This dataset is valuable for trend detection, drought frequency analysis, and model validation. It can support researchers, planners, and policymakers in climate impact studies, early warning systems, and resource management. The data are freely accessible, promoting reproducible research in drought monitoring across Austria.